Program kreatif, dan Pemberdayaan melalui kegiatan Belajar yang menyenangkan di Buku Jalanan Chow Kit (BJCK) di Malaysia - Susriyanti, Susriyanti; Nardo, Rio; Huvaid, Sevilla Ukhtil; Istianingsih, Nanik; Yeni, Fitri; Putra, Aidil (Jurnal Pengabdian Masyarakat Akademisi, 2026)
This community service activity was carried out for students at BJCK (Buku Jalanan Chow Kit) Kuala Lumpur Malaysia. This activity is an international PKM or International Multidisciplinary Community Service (IMCS) activity held by the Indonesian Community Service Lecturers Association (ADPI) in November 2025. This service is entitled "Conducted at Buku Jalanan Chow Kit (BJCK) Program Focused On: Healthy, Creative, and Empowered Children: Learning Through Fun Activities". Buku Jalanan Chow Kit (BJCK) is a non-governmental organization (NGO) as well as an alternative learning center established to address the problem of disparity in access to education for vulnerable children in the Chow Kit area, Kuala Lumpur, Malaysia. The Chow Kit area is known as one of the urban areas with a high level of social vulnerability, inhabited by low-income families, migrant workers, refugees, and undocumented children or stateless children. This condition causes many children to be unable to access formal education provided by the Malaysian government. PKM provides education to students to develop self-confidence, leadership, creativity, communication, and collaboration skills as part of the child empowerment process. Theoretically, this activity can provide a forum for sharing knowledge and experience for us lecturers, teachers, and administrators at BJCK. This concept is implemented through educational games, icebreakers, arts and crafts, storytelling, interactive quizzes, and group activities designed to provide children with a fun learning experience. In activities at BJCK, learning takes place in a community environment so that interactions between volunteers, lecturers, students, and children create a collaborative and contextual learning process.